Linee per una morfologia della storia: gli orizzonti metodologici e disciplinari della ricerca storica da Heinrich Wölfflin a Ernst Cassirer (Itinera, 2012)
Cassirer’s late theory on historical knowledge as symbolic form grows side by side with his plan for a philosophical anthropology. This essay aims to point out how the morphological tradition as well as the works of Heinrich Wölfflin concerning the history of fine arts plays an important role in Cassirer’s definition of the Logic of Humanities and, specifically, of the historical object and its related methodology. In An Essay on Man and in Yale’s seminar Philosophy of History, Cassirer discovers in historical knowledge a problematic symbolic form.